无孔不入的目光 ：论韩丽珠的窥视叙事 = Pervasive sight : Han Lizhu's peeping narration - 王英慧 Wong, Evon (2017)
“窥视”作为人性的本然，是隐蔽的心理投射。然而，在韩丽珠的作品当中，“窥视”却是那样的公然又合理，似乎个人隐私必然就该“被窥视”。韩丽珠，香港新生代具潜能的作家，曾获得多个文学奖项与肯定。然而，关于韩丽珠的研究却寥寥无几。抛开韩丽珠主流的“异化”及“家庭伦理”等主题研究，本文旨在发掘隐匿于多个作品当中，起着隐隐然辅助作用的“窥视”叙事，并发掘窥视行为对于私人空间的扭曲，甚至瓦解的心理，夹杂于性别及阶级的斗争中，互相拉锯的张力。本文主要分为三大部分：一着重探讨福柯的权力论及卡夫卡对于韩丽珠的影响研究，并以此为理论基础。二为韩丽珠作品下的窥视叙事，划分出韩丽珠作品中窥视的角度与叙事方式。三则主要探讨被窥视对象的处境，从性别及阶级的角度切入，揭露社会的权力问题。韩丽珠的作品迂回晦涩，像是不可能的想象，却又是那么真实的投射，亦有心理深入的剖析，也有社会荒谬性的投射。当中，无非有很大的研究空间。而本文即从韩丽珠的窥视叙事着手，结合福柯的理论，以期开拓另一研究视角。"Peep" as the nature of human habit, is a hidden psychological projection. However, the "peep narrative" in Han Lizhu’s fiction becomes open and reasonable, seems like personal privacy should "be peep". Han Lizhu, the Hong Kong's new generation of potential writers, has achieved a number of literary awards. However, there were only a few research papers on Han Lizhu. Despite the theme of "alienation" and "family ethics", this paper aims to explore the distortions of peeps in private space and collapse of the psychology. It contained with gender, political struggle and the tension between each other. This paper is divided into three parts: First will focus on the study of Foucault and Kafka as a theoretical basis that impact in Han Lizhu’s fiction. Second part will analysis the angle and narrative way of Han Lizhu's fiction about “peep” theme. Lastly, it will focus on the subject of peeping from the perspective of gender and society status. It aims to expose the jurisdiction and authority mechanism of society. Han Lizhu’s fictions are roundabout and obscure, like imagination, but also like projection of reality. There have psychological analysis and also social problems. This paper aims to explore the peep narrative research with a view to expanding readers' understanding of the relationship between human psychology and society, and hope to open up another research perspective on Han Lizhu.